How do pedestrians respond to adaptive headlamp systems in vehicles? A road-crossing study in an immersive virtual environment. (September 2021) - Subramanian, Lakshmi D.; O'Neal, Elizabeth E.; Roman, Aldrin; Sherony, Rini; Plumert, Jodie M.; Kearney, Joseph K.
Highlights: Adaptive Headlights Systems (AHS) can increase pedestrian road-crossing safety. Pedestrians choose larger gaps to cross when vehicles are equipped with AHS. The color and timing of icons projected on the road influences AHS effectiveness. Exposure to AHS may result in safer gap choices even with non-AHS vehicles. Abstract: Three-fourths of pedestrian fatalities in the U.S. occur in the dark (National Center for Statistics and Analysis, 2020 ). Adaptive Headlight Systems (AHS) offer the potential to address this problem by improving the visibility of pedestrians for drivers and alerting pedestrians to approaching vehicles. The goal of this study was to investigate how pedestrians respond to different types of AHS. We conducted a mixed factor experiment with 106 college-age adults using a large-screen pedestrian simulator. The task for participants was to cross a stream of continuous traffic without colliding with a vehicle. There were four AHS treatment conditions that differed in the color (white or red) and timing of an icon projected on the roadway in front the participant as an AHS vehicle approached. Participants in the treatment conditions encountered a mix of AHS and non-AHS vehicles. There was also a control condition in which participants encountered only non-AHS vehicles. We found that the color and the timing of the icon projected on the roadway influenced the size of the gaps crossed. Participants in the red icon with early onset condition chose the largest gaps for crossing. An unexpected outcome was that participants in the AHS treatment conditions chose larger gaps even when crossing in front of non-AHS vehicles, suggesting that experiences with AHS vehicles generalized to non-AHS vehicles. We conclude that AHS can have a significant, positive impact on pedestrian road-crossing safety.